Transabdominal Preperitoneal inguinal hernia repair leading to orchiectomy: A case report. (August 2022) - Kefalas, Charalampos; Karlafti, Eleni; Zatagias, Apostolos; Karakatsanis, Anestis; Tsakiris, Georgios; Michalopoulos, Antonios; Paramythiotis, Daniel
Abstract: Introduction: And importance: The most common postoperative complications after inguinal hernia repair are hernia recurrence, hematoma, seroma, wound infection, chronic pain, numbness and swelling. The aim of this case report is to present a rare complication of inguinal hernia repair, a large scrotal abscess that was caused by an inoculated scrotal hematoma 3 months after Transabdominal Preperitoneal bilateral inguinal hernia repair. Case presentation: An 84-year-old patient presented to the emergency department complaining about fever, pain and progressive swelling of the left hemiscrotum. He had undergone a Transabdominal Preperitoneal bilateral inguinal hernia repair 3 months earlier and a scrotal paracentesis 17 days earlier due to a scrotal hematoma. The pelvic CT scan was indicative of a large abscess in the left hemiscrotum compressing the ipsilateral testicle. Surgical exploration of the inguinal area was performed and considering the patient's advanced age the abscess was excised "en bloc" with the ischemic ipsilateral testicle. The patient had an uneventful recovery and was discharged home on the third postoperative day. Clinical discussion: Scrotal abscess, although rare, should be considered in the differential diagnosis of scrotal pain after inguinal hernioplasty. Scrotal drainage is sometimes used in order to relive the patient's discomfort caused by a swollen scrotum, but if not performed properly it can lead to serious infections. Postoperatively, a suction drain or elevation and compression of the scrotum may prevent scrotal complications. Conclusion: Scrotal abscess is a rare complication of inguinal hernioplasty. Scrotal care pathways establishment after inguinal hernia repair could help reduce and manage complications. Highlights: Scrotal abscess is a rare complication of inguinal hernia repair. This is the first reported case of a scrotal abscess leading to orchiectomy following an inguinal hernia repair. Scrotal care pathways establishment after inguinal hernia repair could help reduce and manage complications.